Development and Implementation of Junior High School Health Information System in Serang City - Vina Oktiarina; Yayat Ruhiat; Ujang Jamaludin (Jurnal Penelitian Pendidikan IPA, 2024)
The health information system in schools has a crucial function in supporting the implementation of the School Medical (UKS) program. This study aims to evaluate how effective the health information system developed, "KesSekolah," is based on the opinions of experts in the field of learning media and learning materials. The research approach used is quantitative by conducting user acceptance testing (User Acceptance Testing, UAT) involving experts. The results of the study revealed that this system received a very good rating in terms of the feasibility of learning media, reliability, interface display, and ease of use. The highest value is in the usefulness of the media indicating that this system can improve the UKS program and is feasible to be implemented to improve health standards in the school environment